Coal combustion residues from pulp and paper mills for potential applications. Issue 23 (1st December 2016) - Sultana, Firoza; Rano, Ruma
ABSTRACT: Coal combustion power stations generate huge quantities of ash annually; thus, utilization of such waste residues is an important and essential component for sustainable disposal and management. This paper summarizes an investigation carried out on the coal combustion residues (CCRs) collected from Cachar Paper Mill, Assam, India. A thorough characterization of ash has been carried out with respect to its physicochemical, mineralogical, and morphological features by using density determination, loss on ignition (LOI) determination, Fourier transform infrared, X-ray diffraction, X-ray fluorescence, scanning electron microscopy with electron dispersive X-ray, etc. . The coarser fraction appears to contain a high percentage of char, semi-coked/coked carbonaceous particles, and exceptionally high LOI (86%) values. The carbonaceous matters contain some aliphatic carbon, which implies incomplete combustion. For correlating the total characteristic features, various experiments were performed based on which a number of possible potential utilization directions were suggested. Furthermore, the coarser particles showed excellent water-holding capacities (WHCs, 400%) and good adsorption capabilities, due to the presence of micro- and macropores.